2016
DOI: 10.1021/acs.biochem.6b00958
|View full text |Cite
|
Sign up to set email alerts
|

Reactions of Ferrous Coproheme Decarboxylase (HemQ) with O2 and H2O2 Yield Ferric Heme b

Abstract: A recently discovered pathway for the biosynthesis of heme b ends in an unusual reaction catalyzed by coproheme decarboxylase (HemQ), where the Fe(II)-containing coproheme acts as both substrate and cofactor. Because both O2 and H2O2 are available as cellular oxidants, pathways for the reaction involving either can be proposed. Analysis of reaction kinetics and products showed that, under aerobic conditions, the ferrous coproheme-decarboxylase complex is rapidly and selectively oxidized by O2 to the ferric sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
34
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(38 citation statements)
references
References 46 publications
2
34
0
Order By: Relevance
“…Moreover, the 14 s half-life for the initial decarboxylation of P2 to yield harderoheme and the circa 300 s lifetime of the radical species overall suggests that the observed EPR signals most likely represent superimposed radical intermediate density from both the decarboxylations of P2 and P4, particularly at the later time points (7). This observation is consistent with prior stopped flow analyses, which showed that the P2 and P4 decarboxylations were similar in rate and not temporally well resolved (8).…”
Section: Resultssupporting
confidence: 85%
See 1 more Smart Citation
“…Moreover, the 14 s half-life for the initial decarboxylation of P2 to yield harderoheme and the circa 300 s lifetime of the radical species overall suggests that the observed EPR signals most likely represent superimposed radical intermediate density from both the decarboxylations of P2 and P4, particularly at the later time points (7). This observation is consistent with prior stopped flow analyses, which showed that the P2 and P4 decarboxylations were similar in rate and not temporally well resolved (8).…”
Section: Resultssupporting
confidence: 85%
“…Each decarboxylation is an oxidation in which a net two electrons and two protons are transferred from the reactive propionate to a molecule of H2O2, yielding 2H2O, CO2, and a new vinyl group (7,8). H2O2 activation at the open coordination position on the substrate iron (distal pocket) could generate any of a number of well-known reactive species, including a ferric-hydroperoxy [Fe(III)-OOH], ferryl porphyrin π-cation radical [Fe(IV)=O (por+•), compound I], or ferryl complex [Fe(IV)=O or Fe(IV)-OH compound II].…”
mentioning
confidence: 99%
“…S6). 22 These results suggest that the Mn(III)coproheme binds in the catalytic orientation but is incapable of activating H 2 O 2 and therefore is stable as a solid state complex in the presence of O 2 and ionizing X-ray radiation, conditions under which H 2 O 2 may be spontaneously produced.…”
Section: Resultsmentioning
confidence: 90%
“…36 Prior work showed that the second order reaction between the decarboxylase-coproheme complex and H 2 O 2 , which leads to the ferric heme b complex, accelerates with pH (~3-fold, p K a = 7.4) and is solvent-isotope dependent (average k (H 2 O): k (D 2 O) = 2.2). 22 Both results suggest the involvement of proton movement in the rate limiting step of the H 2 O 2 reaction. However, pH has a much larger influence over the analogous, acid-base-catalyzed steps in heme peroxidases.…”
Section: Resultsmentioning
confidence: 91%
See 1 more Smart Citation